Penyesuaian Sosial Anak Gifted - Iswinarti (ANIMA Indonesian Psychological Journal, 2002)
In fact, many people don't know much about gifted children. More over, they are frequently suspected as "trouble makers". This research is an explorative research study with the aim to depict the social adaptation of gifted children. Subjects are students (N = 11; 5 girls and 6 boys), aged 5.5-1 1.5 with IQ's above 130. Subjects are selected through: (a) Colour Progressive Matrics (CPM) and Standard Progressive Matrics (SPM) tests, (b) Binet or WISC or CFIT tests to obtain their IQ's. The social adaptation ability was obtained through a social maturity test, interview, and observation. Results show, most of the subjects are able to adapt to other people.